PREVALENCE OF DENGUE HEMORRHAGIC FEVER IN BALI FROM 2015 TO 2020 AND DURING THE COVID-19 PANDEMIC - I Made Dwi Mertha Adnyana; Farachatus Salwa Salsabila Azhari; Ni Luh Gede Sudaryati (Jurnal Berkala Epidemiologi, 2022)
Background: Dengue hemorrhagic fever cases increased significantly during the COVID-19 pandemic phase. Purpose: This study defines, describes, and evaluates the dengue hemorrhagic fever incidence in Bali Province from 2015 to 2020 and in the context of the COVID-19 pandemic. Methods: The various types of descriptive study with case series design. The study used an environmental epidemiology approach to analyze the health profile of Bali Province. The number of DHF cases in 2015-2020, DHF-related morbidity and death rates, larva-free rates, climate, population and population density, and gender were variables in this study. The study took place in May and June 2021. Results: The prevalence of dengue hemorrhagic fever in the province of Bali fluctuated between 2015 and 2020. The highest number of dengue cases in 2016 was 20,306, and they fell from 2017 to 2019. Cases doubled in 2020, up by 12,173. The endemic areas with the highest prevalence of cases are in the districts of Buleleng and Badung. The highest incidence rate was in 2016 at 483/100,000 population, and for the last five years, it has not met the national target of 49/100,000 population. The highest CFR figure in 2020 was 0.43%, an increase of 1.5 times during the COVID-19 pandemic. Conclusion: The prevalence of dengue hemorrhagic fever cases in Bali in 2015 – 2020 fluctuated significantly, and mortality due to dengue during the COVID-19 pandemic experienced a significant increase.